Health centres for orang asli - The Star, (2012)
AJINOMOTO (Malaysia) Bhd recently sponsored and carried out its Corporate Citizenship Day at orang asli villages of Kampung Penderas and Kampung Pasu in Kuala Krau, Pahang.